1982
DOI: 10.1161/01.cir.65.6.1052
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of right ventricular function during supine bicycle exercise after Mustard's operation.

Abstract: SUMMARY Right ventricular (RV) performance during supine bicycle exercise was evaluated by gated equilibrium nuclear angiography in 19 clinically well children with d-transposition of the great arteries (d-TGA), 6.4 ± 2.7 years after Mustard's operation. Comparisons were made between rest and peak exercise. The mean resting ejection fraction was 44 ± 12% (range 30-75%) and was unchanged at peak exercise. Eight children had a normal ejection fraction response, whereas 11 children had either no increase or a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(34 citation statements)
references
References 36 publications
1
33
0
Order By: Relevance
“…Firstly, the morphologic right ventricle may not be able to meet the requirements of a systemic ventricle. [4][5][6] Secondly, a low heart rate (HR) response during exercise 7 may cause limited exercise performance. And finally, a relative preload reduction during exercise caused by the rigid atrial baffles may limit exercise performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the morphologic right ventricle may not be able to meet the requirements of a systemic ventricle. [4][5][6] Secondly, a low heart rate (HR) response during exercise 7 may cause limited exercise performance. And finally, a relative preload reduction during exercise caused by the rigid atrial baffles may limit exercise performance.…”
mentioning
confidence: 99%
“…And finally, a relative preload reduction during exercise caused by the rigid atrial baffles may limit exercise performance. 8,9 However, those previous studies assessed patients after the atrial switch operation either without a control group [4][5][6]9 or by comparing them to normal subjects with morphologic left ventricles in systemic position. 7,8 The ideal control group for examining the cause of limited exercise performance of patients after the atrial switch operation is very rare because it comprises patients with congenitally corrected transposition of the great arteries (ccTGA) who have not had previous heart surgery.…”
mentioning
confidence: 99%
“…We believe that patients whose RVEF is approximately t/ normal or less 0 .33) have some impairment of exercise tolerance although to date we have not been able to quantify this by standardized exercise testing . Benson et al [2] showed an abnormal exercise response in terms of either a fall or no change in RVEF during exercise in 9 of 15 asymptomatic patients studied 3 .5 to 15 years after a Mustard repair . These data strongly suggest that abnormal systemic ventricular function may be a significant long-term problem in the postoperative adolescent and adult who have had an intraatrial repair .…”
Section: Right Ventricular Dysfunction J3mentioning
confidence: 99%
“…Patients are at increasing risk of late ventricular dysfunction and sudden cardiac death. [2][3][4][5][6][7][8][9][10][11] The exact underlying pathophysiological mechanism is likely to be multifactorial. Myocardial ischaemia in the morphologically right systemic ventricle has been suggested based on the presence of perfusion defects, 9 wall motion abnormalities and features suggestive of fibrosis on late gadolinium cardiovascular magnetic resonance (CMR).…”
Section: Introductionmentioning
confidence: 99%